What are physical exercise interventions in older age? Literature review for physical and cognitive function - Didi Suryadi; Ahmad Nasrulloh; Jeki Haryanto; Y Touvan Juni Samodra; Isti Dwi Puspita Wati; Mikkey Anggara Suganda; Sigit Nugroho; Procopio B. Dafun Jr; BM. Wara Kushartanti; Ella Fauziah (IP Iermakov S.S., 2024)
Background and Study Aim. The elderly represent a growing age group and an integral part of modern society. The aging process introduces significant health challenges, making exercise an essential component in maintaining quality of life and well-being among the elderly. This study reviews the impact of physical exercise interventions on the physical and cognitive functions of the elderly population. Material and Methods. The search for this study was conducted using the ScienceDirect and PubMed databases. The search strategy employed a combination of keywords ("Elderly Physical Exercise" AND "Physical Exercise Intervention" AND "Elderly Fitness and Cognitive" AND "Physical Exercise for Physical and Cognitive Functions" AND "Physical and Cognitive Benefits" AND "Elderly Physical Exercise Prevalence"). This search adhered to the PRISMA guidelines. Initially, 1,854 publications were identified through the database searches (ScienceDirect: 981 articles; PubMed: 873 articles). After applying the exclusion criteria, only 11 articles remained. Results. It has been found that physical exercise interventions for the elderly significantly impact their physical and cognitive functions. In the first group, exercises such as home-based e-Health programs, multicomponent exercises, moderate aerobic exercises, dance training, and balance training have been identified. All these have been shown to provide substantial benefits. These programs enhanced not only physical function but also cognitive performance and the overall quality of life for older adults without physical and cognitive health complaints. This showcases the potential of physical exercise interventions to prevent morbidity and reduce disability. The second group focused on physical exercise interventions for older adults with degenerative disease complaints, such as type 2 diabetes and multiple sclerosis. Dual-task exercise programs and tai chi chuan exercises have demonstrated improvements in cognitive function for this demographic. They also improved physical fitness. The research also points out some limitations related to the implementation and budgeting for these programs. Conclusions. The literature review suggests that physical exercise interventions play a crucial role in maintaining physical and cognitive functions in older adults. Exercise programs tailored to the specific health conditions of individuals can significantly improve the quality of life and reduce the risk of declining physical and cognitive functions in the elderly population.